(untitled) (Aintelia Science Notes, 2022)
As it is known, steam is used in many industrial facilities. If steam at different pressures is used in processes within the facility, the pressure of the steam must be reduced. A pressure reducer is used to reduce the vapor pressure with conventional methods. Electricity can be generated by removing the pressure reducer and replacing it with a micro steam turbine. Such a system not only allows the production of the heat energy needed by the facility without interruption, but also enables the generation of additional electrical energy in the facility. The aim of this study is to investigate the thermo-economic analysis of such a system. In the analysis, the situation where 5 tons/h of steam is produced at 10 bar pressure and then drops to 5 bar is chosen as the base case. Under these conditions, 44.35 kW electrical power is obtained from the turbine. The internal rate of return and the payback period are calculated as 41.17% and 4 years and 11 months, respectively.